Congenital hairy melanocytic nevus over eye - Sunil Kumar Gupta; Sushantika Kumari (Wolters Kluwer Medknow Publications, 2022)
A ten year old boy presented with black hairy nevus over left eyelid since birth.He did not have any complains of vision. The nevus was progressing in size encroaching over upper eyelid with minute papules in eyelid margin. It was diagnosed as congenital hairy melanocytic nevus clinically. His parents were advised laser therapy after he reaches maturity as a management option. The location of the nevus made it worth reporting.